Transformation of initial cartographic materials for the “Main State Topographic Map” to coordinate system UCS-2000 - Karpinskyi Yurii; Lazorenko Nadiia; Kin Danylo; Vitruk Olga (Polish Cartographical Review)
Initial cartographic materials were determined to create the topographic database of the “Main State Topographic Map”. They require preparation for creating (updating) digital topographic maps at the scale of 1:50,000. One of the stages of preparation of input cartographic materials is their transformation to the coordinate reference system UCS-2000. The goal of the article is to research the problem of transformation of points coordinates by the rigorous mathematical method for referencing cartographic materials from the coordinate systems CS-42/CS-63 to the State Geodetic Coordinate Reference System UCS-2000 (after this – UCS-2000) by geographic information systems (GIS) for creation (updating) digital topographic maps at the scale of 1:50,000 to create the seamless topographic database of the “Main State Topographic Map” on the territory of Ukraine. Authors propose a method of transformation orthophoto at the scale of 1:10,000 to UCS-2000 in Cartesian coordinates of Gauss-Krüger projection in the corresponding 6-degree zone in the adopted state interchart of topographic maps at the scale of 1:50,000. This method consists of cartographic materials transformation using a transformation field in the form of a GRID model based on the triangulation TIN model using the finite element method. The choice of the finite element method and the peculiarities of affine transformation are mathematically substantiated. Also, the authors determined the requirements for the method of coordinates transformation.